Analysis of Employee Performance through Compensation, Work Motivation, and Work Discipline at PT. Sinar Jernih Sarana - Sania Yahira; Yosafat Puji Hastoko (Formosa Journal of Science and Technology, 2023)
This study aims to determine whether there is an influence of employee performance analysis through compensation, work motivation, and work discipline at PT Sinar Jernih Sarana. This research uses accidental sampling research technique with non-probability sampling. Employees of PT Sinar Jernih Sarana became the population in this study with a total of 100 people who could be used as a sample of people who happened to meet the researcher considered suitable as a data source. This research method is quantitative research using multiple linear regression analysis techniques. The results of this study show that compensation has a significant effect on employee performance, motivation has a significant effect on employee performance, work discipline has a significant effect on employee performance at PT Sinar Jernih Sarana. Simultaneously these three variables have a significant effect on employee performance at PT Sinar Jernih Sarana.